The Daily Sniff - Cabrera, Jane (Cabrera, Jane. Jane Cabrera's story time., 2023)
"Ted, a dog who gets his news each day by smelling out The Daily Sniff, investigates when his town is overcome by an usual odor, which turns out to be a skunk family"--